2019
DOI: 10.1097/scs.0000000000005614
|View full text |Cite
|
Sign up to set email alerts
|

Novel Technique and Step-by-Step Construction of a Computer-Guided Stent for Mandibular Distraction Osteogenesis

Abstract: Introduction: Distraction osteogenesis is an integral part in management of mandibular defects associated with hemifacial microsomia and post-ankylotic mandibular defects. The most difficult part in distraction osteogenesis is the prediction of distraction vector and risk of injury to vital structures as inferior alveolar. The present study aimed to present 3-dimensionally constructed computer-guided splints in distraction osteogenesis to get an ideal vector and minimal risk of vital structures inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Hany et al report a small series of cases integrating virtual planning and 3D printing of surgical stents to protect relevant anatomical structures and an acceptable therapeutic margin of error in the vectors of mandibular osteogenic distraction be controlled from planning. [10] On the other hand, Bertossi et al demonstrated the advantage of performing an orthognathic surgery with an ultrasonic cut against conventional cutters. They showed that the ultrasonic cutter gives a more proper cut and decreases bleeding risk due to soft tissue protection around osteotomies than conventional ones.…”
Section: Discussionmentioning
confidence: 99%
“…Hany et al report a small series of cases integrating virtual planning and 3D printing of surgical stents to protect relevant anatomical structures and an acceptable therapeutic margin of error in the vectors of mandibular osteogenic distraction be controlled from planning. [10] On the other hand, Bertossi et al demonstrated the advantage of performing an orthognathic surgery with an ultrasonic cut against conventional cutters. They showed that the ultrasonic cutter gives a more proper cut and decreases bleeding risk due to soft tissue protection around osteotomies than conventional ones.…”
Section: Discussionmentioning
confidence: 99%
“…Several treatment modalities have been proposed for the management of the deformity depending on the case severity as distraction osteogenesis. 12 Genioplasty was among the modalities applied for the treatment of mandibular asymmetry, especially the less severe cases. The other point that encouraged our team to conduct this study is the fact that digital techniques will end the use of conventional planning and will improve the quality oforal rehabilitations, the postoperative results, and the perception by patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on all of the above we decided to use the finite element analysis in the current study; to compare and simulate the use of intraoral and extraoral distractors in the management of hemifacial microsomia. 21 The biting force values used in the current study were based on a recent observational study done on 20 hemifacial microsomia patients at the Plastic and Reconstructive Surgery Division of the ''Dr Manuel Gea Gonzalez'' General Hospital in Mexico City for 1 year between January and December 2016. The study was conducted by Telich-Tarriba et al 22 ; the study found that the mean biting force in the hypoplastic side was 22.71 and 14.05 kgF on the normal side; however, we changed units into 222.7 and 137.78 N on the defective and normal side respectively to applicable with the software we used.…”
Section: Discussionmentioning
confidence: 99%
“…Based on all of the above we decided to use the finite element analysis in the current study; to compare and simulate the use of intraoral and extraoral distractors in the management of hemifacial microsomia 21 …”
Section: Discussionmentioning
confidence: 99%